Association of laboratory parameters and genetic polymorphisms with ischemic stroke in Chinese Han population - Wang, Jiayong (Exp Ther Med, 2021)
Numerous genetic polymorphisms and clinical laboratory parameters are associated with ischemic stroke (IS). However, the results of such studies have frequently been inconsistent. The aim of the present study was to evaluate associations between clinical laboratory parameters with genetic polymorphisms that influence the risk of IS in a Chinese Han population. Clinical laboratory parameters were measured by an automatic biochemical analyzer. Genotype and allele frequencies of the polymorphisms angiotensin-converting enzyme (ACE) D/I, methylene tetrahydrofolate reductase (MTHFR) C677T and β-fibrinogen (β-Fg) A/G, 455/148T/C were characterized by restriction fragment length polymorphism-PCR. Furthermore, the gene polymorphisms plasminogen activator inhibitor (PAI)-1-4G/5G and apolipoprotein E (ApoE) ε2,3,4 were characterized by allele-specific PCR. The associations of genotype and allele frequencies of the six risk genes in different groups with clinical laboratory parameters were analyzed by chi-square tests. The distribution maps of the polymorphisms of the six genes and clinical laboratory parameters were compared between a control group of 336 healthy individuals and 762 patients with IS. Certain laboratory parameters were associated with ACE I/D, β-Fg-455 A/G and PAI-1 4G/5G. The D allele of ACE I/D was associated with high levels of total cholesterol and low-density lipoprotein cholesterol (LDL-C). Furthermore, high levels of fasting blood glucose, triglyceride and LDL-C were risk factors for IS. There were significant differences in the genotype frequencies of ACE I/D, β-Fg-455 A/G and β-Fg-148 T/C between the IS and the control group. In conclusion, clinical laboratory parameters were associated with the risk of polymorphisms of IS-related genes. The present results support the determination of a range of control values of clinical laboratory parameters for common genotypes in patients with diabetes and hyperlipidemia as a strategy for the early prevention of IS.